Ethical Issues in Cosmetic Surgery for Women: Self-Actualization or Manipulation? - Nurulfatmi Amzy (Human Narratives, 2019)
The technology of plastic surgery has been beneficial to mankind around the world. Plastic surgery can help people to retain and regain the function on some part of the body that was damaged. However, plastic surgery came with a handful of ethical issues. With the ability to alter one’s own body, many women sought to use this technology to beautify themselves. This part of technology then later was named as cosmetic surgery. By the reasoning of self-autonomy and free will, a person can easily alter their own physique according to their own will. This paper aimed to analyze this phenomenon based on philosophical thoughts regarding aesthetic purpose where it argued that beauty is a construction of media and society, not a construction that came from within one’s self. This paper argued that cosmetic surgery technology preyed upon women and instead of firming the position of self-autonomy and free will; it degrades women as a human of free will. The over-application of technology will only objectify women and it poses a danger as it can be used as a tool to satisfy certain interests